2017
DOI: 10.1515/pterid-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Medical significance of simultaneous application of red blood cell distribution width (RDW) and neopterin as diagnostic/prognostic biomarkers in clinical practice

Abstract: In our individual and collaborative studies, we have played a part in pioneering investigations on the usefulness of biomarkers -red blood cell distribution width (RDW) and neopterin. This mini review includes historical data on the topic and is related to the first contributions in this field, as well as to the possibilities for further improvement and simultaneous application of RDW and neopterin measurements in the prevention, prognosis and treatment of a great number of socially important disease condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…RBC indices and anemia are precursors for HIV-1-associated neurocognitive disorders . Furthermore, the ageing of RBCs and their disposition in the spleen are portent by spicules formed on the cell surface (echinocytes). , Thus, the absence of morphological changes in RBCs is a prerequisite in HIV. The SEM image of RBCs treated with Efa–Enf Co-loaded PLN, blank PLN, and normal saline (negative control) portrayed a healthy biconcave-shaped RBC morphology, while positive control images revealed an irregular morphology with pore formation and echinocytes.…”
Section: Resultsmentioning
confidence: 99%
“…RBC indices and anemia are precursors for HIV-1-associated neurocognitive disorders . Furthermore, the ageing of RBCs and their disposition in the spleen are portent by spicules formed on the cell surface (echinocytes). , Thus, the absence of morphological changes in RBCs is a prerequisite in HIV. The SEM image of RBCs treated with Efa–Enf Co-loaded PLN, blank PLN, and normal saline (negative control) portrayed a healthy biconcave-shaped RBC morphology, while positive control images revealed an irregular morphology with pore formation and echinocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have revealed that RDW is also associated with liver, kidney, and cardiovascular diseases. In addition, RDW is known to be a recently used inflammation marker in inflammatory diseases, such as septic shock, inflammatory bowel disease, and acute appendicitis (19,(35)(36)(37). In addition, RPR has been shown to be a new and rapid laboratory index for predicting mortality in many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Others have previously posited RDW to be indicative of poor cancer prognosis. [21][22][23][24][25] A multivariable analysis of the data showed recurrences correlated with age and pathologic T stage, but not RDW (Table 4).…”
Section: Discussionmentioning
confidence: 99%